Effects of soil-structure interaction on the excitation and response of a medium-rise reinforced concrete building - Hannes Garðarsson 1966- (2012)
It is common tradition in Iceland to found structures on compact gravel cushions. This differs from foreign traditions where it is more common to found structures on piles where the soil is thick. The topic of this study is a phenomenon commonly called soil-structure interaction, i.e. how the dynamic properties of a thick gravel foundation work together with the dynamic properties of an attached structure. In the project a 13 storey reinforced concrete residential building is examined. Monitoring system has collected acceleration data in the building since 2007. System identification of the structure is performed based on earthquake recordings from the data set. The dynamic characteristics of the 7 meter thick gravel cushion, which the building is founded on, are examined. The building is modelled applying the finite element program SAP2000. The dynamic properties of the foundation are examined by using spring supports for the building and the overall differences in the dynamic properties compared to a fixed supported building are evaluated. The structural model including the spring supports is calibrated based on the results from the system identification of the structure to ensure that the model represents the dynamic characteristics of the structure. Then response spectrum analysis is conducted for fixed base and spring supported model and the results compared. It was found that natural frequencies of the structure, estimated by FE-model, significantly depend on the supporting conditions. The response spectrum analysis showed that the dynamic forces proved to be significantly higher for the spring supported model than for the fixed base model. Therefore it is important, in the design process of reinforced concrete structures, to take the influence of dynamic properties of the foundation into account when structures are modelled and analysed. Áhrif samverkunar malarpúða og mannvirkis á örvun og svörun bygginga úr járnbentri steinsteypu Algengt er að byggingar á Íslandi séu grundaðar á þjöppuðum malarpúða. ...